Chronic postoperative pain after non-intubated uniportal VATS lobectomy - Farkas, Attila; Csókási, Tímea; Fabó, Csongor; Szabó, Zsolt; Lantos, Judit; Pécsy, Balázs; Lázár, György; Rárosi, Ferenc; Kecskés, László; Furák, József (Frontiers in Surgery, 2023)
Introduction: Patients undergoing thoracic surgery are at increased risk of developing, long-lasting pain. Beyond the non-surgical factors, the type of operation, including the number of incisions, and the anesthetic assessment seemed to be important factors, although some studies are controversial. The aim of our study was to examine the presence of chronic postoperative pain after non-intubated uniportal VATS lobectomy. We examined the difference between the intubated, relaxed and nonintubated spontaneous ventilation surgical approaches in patients who underwent video-assisted thoracoscopic (VATS) uniportal lobectomy.Methods: Demographic and postoperative data were retrospectively collected and analyzed , focusing on the use of pain medications, in 67 patients of the 140 patients selected by propensity score matching who underwent intubated (iVATS) or non-intubated (NITS) uniportal VATS lobectomy. This study focused on the use of analgesic medications 3, 6, and 12 months after surgery.Results: Thirty-five intubated and 32 non-intubated patients were compared. Although the analgesic consumption was nearly 2% higher among the iVATS patients during the follow-up period, there were no statistically significant differences at 3 months (15.6 vs. 17.1%) (p=0.868), at 6 months (9.4 vs. 12.4%) (p=0.785), and at 12 months (3.3 vs. 5.9%) (p=0.633) between the NITS and iVATS groups, respectively. More female than male patients reported chronic pain, but the difference was not statistically significant (p=0.616). Diabetes mellitus was a statistically significant cofactor This is a provisional file, not the final typeset article associated with chronic pain (p=0.03), while cardiac disease (p=0.6), perioperative morbidity (p=0.228), prolonged air leak (p=0.057), and repeat drainage (p=0.626) were not.Our study suggests that after non-intubation VATS lobectomies, the postoperative pain was less at 3, 6, and 12 months in NITS patients compared to iVATS patients. The 2% difference was not significant, so it may not be appropriate to claim the advantages of NITS in terms of postoperative pain.